SENSUAL ADVERTISING TVC “AXE UNIVERSITY” SEBAGAI REPRESENTASI KAPITALISME MEDIA DAN HYPERREALITAS PEREMPUAN INDONESIA - Ardhariksa Zukhruf Kurniullah (SEMIOTIKA: Jurnal Komunikasi, 2015)
Sensual Advertising is advertising using sex appeal. Ads with female existence can not be separated, because women have the power to help selling the product being advertised. Researchers chose version TVC ad AXE University in 2014 as an advertising being analyzed as this ads shows the presence of symptoms and the exploitation of the female body as a representation of capitalism media. This research aims to analyze the presence of women in the AXE deodorant ad became a major commodity, knowing the media representations of capitalism and female hyperrealitas Indonesia in the ad TVC "Axe University" .and analyzing the connotation and denotation of meaning contained in the body language of women who are at AXE deodorant ad.Research on AXE ad TVC uses the type of visual analysis of qualitative research with the aim to dismantle an object of analysis, in this case the visual image AXE ads containing construction meaningful symbols which call for interpretation. Data collection techniques used in this study is the analysis of the documents in the form of object data on ad ad campaign TVC AXE AXE University 2014 version of the data analysis techniques used in this study is a qualitative analysis using semiotics. Data in the form of ad ad campaign ads TVC AXE AXE University 2014 version.The results of the study took advantage of advertising sensual sensuality as its appeal. Sensual advertisement contained in the version of the Axe Axe TVC University has meaning as an attraction, so sensual advertising should be able to cause a feeling or interest to any destination of his own advertising. Sensual is a way of advertising a product to captivate the audience / consumer. Sensual advertising intentionally produced and are made in such a way as a representation of capitalism in the business industry. Women as objects of capitalism in getting profit. So women are always in the process of construction in advertising by capitalists become a commodity in benefit. Keywords: sensual advertising, representation of capitalism, TVC AXE University, hyperrealitas, simulacra.